Coping styles for sexual dysfunction and stress among married women of reproductive age: a cross-sectional study from turkey - Ozdemir, Serpil; Yilmaz, Burcu; Karasahin, Kazim Emre; Yuksel, Cigdem (Journal of the Pakistan Medical Association, 2024)
Objective: To identify sexual dysfunction in married women of reproductive age, and to examine its relationship with stress coping styles. Method: The cross-sectional, descriptive study was conducted between February and June 2019 at the obstetrics and gynaecology outpatient clinic of Gulhane Training and Research Hospital in Ankara, Turkey. The sample comprised married women aged 18-49 years who had an active sexual life over the preceding month, and were neither pregnant nor in the postpartum phase. Data was collected using the Female Sexual Function Index, and the Stress Coping Styles Scale. Data was analysed using SPSS 22. Results: There were 216 women with mean age 33.58±6.77 years. The mean Female Sexual Function Index score was 22.29±6.08. The mean Stress Coping Styles Scale subscale scores were: self-confident 20.71±3.53, helpless 18.07±4.27, submissive 12.13±3.00, optimistic 13.70±2.35, and seeking social support 11.89±2.01. The total Female Sexual Function Index score had a positive, significant correlation with self-confidence (r=0.15; p=0.03) and seeking social support subscales (r=0.18; p=0.01) and a negative, significant correlation with submissive subscale (r=-0.17; p=0.02) of the Stress Coping Styles Scale. Conclusion: Establishing awareness among women about sexual dysfunction and improving effective coping styles may contribute to improved sexual health among women. Key Words: Sexuality, Female, Sexual dysfunction, Coping strategies.